O currículo na organização do ensino das professoras da Educação Infantil - Alvares, Deborah Miranda (2023)
This dissertation developed in the Professional Graduate Program in Education of the Federal University of São Carlos, São Carlos campus, guided by the following question: how the current Curriculum has been used in the organization of the teaching of Early Childhood Education teachers in the city of Bauru/ SP? The general objective of the research is: to identify how the teaching organization carried out by the Early Childhood Education teachers takes place based on the current Curriculum; and as a specific objective: to analyze the organization of the teachers' teaching according to the objective modes of operation. In addition, we are guided by the hypothesis that the appropriation of the Curriculum by the teachers is important for the organization of the work of the teachers and we consider, specifically, that the results of the organization of teaching are a result of the needs and reasons that lead them to propose and to develop activities to enable the transformation of objective reality. Therefore, we believe that the theoretical foundations of the Historical-Cultural Theory guided us to the answer to our research problem and meet the general objective and the specific objective. The research participants are six Early Childhood Education teachers from the city of Bauru/SP. Each has a different length of service and teaches in different geographic regions of the city. We used the following instruments for data production: a semi-structured interview and the “Dynamic Planning of 2019” as a subsidy. In preparing the interview script, we took into account the reasons for the activity, according to Leontiev (2017), and the four aspects of Ibiapina (2008): description, information, confrontation and reconstruction, in order to capture how the teachers used, or not, the elements of the Curriculum in the organization of teaching. We thus arrive at some considerations that unfortunately, the implementation of the current Curriculum left gaps that need to be filled in a concrete way based on in-service training that is effectively guided by the theoretical framework adopted in, and for the elaboration of the Curriculum, such as training in service that needs to be organized based on the historical-cultural theory as a form, that is, the very organization of teaching the Curriculum, aimed at teachers, needs to be based on the fundamentals, since we learn through the way we are taught, in the development of how we teachers will teach.